2022
DOI: 10.24093/awej/vol13no2.4
|View full text |Cite
|
Sign up to set email alerts
|

Development of Intercultural Communicative Competence in the Process of Teaching English to Future Interpreters

Abstract: The successful functioning of both the state and individual in the conditions of updated intercultural communication is impossible without adequate mastery of the universal language of international communication, which is currently the English language. The development of intercultural abilities of future interpreters in the field of business communication is aimed at continuous improvement of existing educational programs of institutions of higher education. The relevance of our research is due to the growin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Sociolinguistic instruction involves the study of language use in social contexts, and authentic materials give students the opportunity to learn how language is utilized in the real world. In this essay, I will discuss the advantages of using authentic materials in elementary school sociolinguistic instruction and provide examples of authentic materials that can be used (Dvorianchykova et al, 2022;Lee, 2020;SevaraBaxodirovna, 2021;Sudiarta & Widana, 2019). An important advantage of using authentic materials in sociolinguistic instruction is that they expose students to real-world language usage.…”
Section: Authentic Materials For Sociolinguistics Teaching In Element...mentioning
confidence: 99%
See 2 more Smart Citations
“…Sociolinguistic instruction involves the study of language use in social contexts, and authentic materials give students the opportunity to learn how language is utilized in the real world. In this essay, I will discuss the advantages of using authentic materials in elementary school sociolinguistic instruction and provide examples of authentic materials that can be used (Dvorianchykova et al, 2022;Lee, 2020;SevaraBaxodirovna, 2021;Sudiarta & Widana, 2019). An important advantage of using authentic materials in sociolinguistic instruction is that they expose students to real-world language usage.…”
Section: Authentic Materials For Sociolinguistics Teaching In Element...mentioning
confidence: 99%
“…Advertisements are designed to persuade and influence consumers to purchase a product, and they provide students with an excellent opportunity to study the language employed to achieve these ends. Students can analyze how language is used to appeal to various audiences and how language varies depending on the advertised product (Dvorianchykova et al, 2022;Fisenko et al, 2021;SevaraBaxodirovna, 2021;Sudiarta & Widana, 2019). News articles are another example of authentic materials that can be used for sociolinguistic instruction.…”
Section: Authentic Materials For Sociolinguistics Teaching In Element...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that intrinsic motivation, self-determination theory, social cognitive theory, and goal-setting theory increase motivation and engagement, whereas extrinsic motivation may not. The optimal strategy for motivating learners depends on the learner's needs, the learning environment, and the task (Dvorianchykova et al, 2022).…”
Section: Goal-setting Theorymentioning
confidence: 99%
“…That is, in addition to the language, it is important to know also the peculiarities of the native culture of your interlocutor. Educational institutions currently face the urgent task of not only developing students' language skills: listening, speaking, reading, writing, grammar and vocabulary, but also developing intercultural English-language communicative competencies (Vu & Dinh, 2022;Dvorianchykova et al, 2022).…”
Section: Introductionmentioning
confidence: 99%